Prevalence of non-fatal injuries and associated factors in Mbarara Municipality, Western Uganda, December 2016-June 2017 - Rebecca Nuwematsiko; Angela Nakanwagi Kisakye; David Musoke; Delia Bandoh; Lillian Bulage; Olufemi Olamide Ajumobi; Frederick Oporia; Fiston Muneza; Nino Paichadze; George Pariyo; Abdulgafoor Bachani; Olive Kobusingye; et al. (Journal of Interventional Epidemiology and Public Health)
Background: Injuries are a significant public health problem but poorly quantified especially in low and middle-income countries. In Uganda, the burden of injuries is poorly quantified with most of the data reported being facility and mortality based. Many non-fatal injuries, therefore, remain unreported in communities. We conducted a household survey in Mbarara Municipality to identify and describe all non-fatal injury events and the associated factors. Methods: We conducted a cross-sectional study of non-fatal injuries among 966 household members in Mbarara Municipality, from May to June 2017. The most recent non-fatal injury (within a six-month recall period; December 2016 to June 2017) resulting in loss of at least one day of usual daily operating activity was considered. We conducted a descriptive statistical analysis to estimate the counts and frequencies of non-fatal injuries. We identified factors associated with non-fatal injuries using a modified Poisson regression model. Results: The prevalence of non-fatal injuries was 18.2% (176/966) with 92% (162/176) of the non-fatal injuries being unintentional. Falls 27.3% (48/176) were the most common cause of injury followed by road traffic injuries (RTI), 26.7% (47/176), burns 16.5% (29/176) and the least being poisoning 2.8% (5/176). Occupation as casual laborer (Adjusted PR=2.1, 95% CI: 1.2 - 3.7), urban residency (Adjusted PR=1.5, 95% CI: 1.1 - 1.9) and being a non-native of the study area (Adjusted PR=1.7, 95% CI: 1.3 - 2.3) were independently associated with non-fatal injuries. Conclusion: Almost one out of five people had suffered a non-fatal injury in the past six months in Mbarara Municipality. Majority of the non-fatal injuries were unintentional, caused by falls and RTIs, and were amongst casual labourers and urban residents. These findings reveal a gap in injury prevention in Uganda that needs to be addressed to improve the quality of life.